Urbanization in the time of climate change: Examining the response of Indian cities. (26th November 2018) - Khosla, Radhika; Bhardwaj, Ankit
Abstract : India's urban transition is salient to the growing emphasis on city responses to climate change. While projected to experience the largest global urban transition with significant infrastructure investment in the next few decades, the welfare of Indian cities remains poor, which complicates the implications for climate change mitigation and adaptation. This paper traces, synthesizes and characterizes the emerging literature on Indian urban climate debates. It discusses the arc of urban climate efforts, from an initial emphasis on climate vulnerabilities and risks, broadening over time to include climate mitigation. The paper examines the governance forms and political motivations with which such actions are pursued in cities and finds three overarching characteristics: the use of local development priorities as an entry point to climate mitigation and adaptation; the role of nonstate actors in promoting climate‐relevant outcomes; and the proclivity for discrete project‐based activities. The paper suggests that while a range of Indian cities are beginning to consider climate concerns, a larger strategic understanding of the interaction between climate and development priorities, across policy and governance levels, is yet to be developed. The future trajectory of urban India's responses to climate change will be shaped by the institutional prioritising, linking and integrating of urgent local development and mitigation and adaptation goals. This article is categorized under: Climate and Development > Urbanization, Development, and Climate Change